2016
DOI: 10.1016/j.neuron.2016.01.034
|View full text |Cite
|
Sign up to set email alerts
|

A Systems-Level Analysis of the Peripheral Nerve Intrinsic Axonal Growth Program

Abstract: SUMMARY The regenerative capacity of the injured CNS in adult mammals is severely limited, yet axons in the peripheral nervous system (PNS) regrow, albeit to a limited extent, after injury. We reasoned that coordinate regulation of gene expression in injured neurons involving multiple pathways was central to PNS regenerative capacity. To provide a framework for revealing pathways involved in PNS axon regrowth after injury, we applied a comprehensive systems biology approach, starting with gene expression profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
436
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(459 citation statements)
references
References 61 publications
22
436
1
Order By: Relevance
“…Although overexpression of ATF3 can promote peripheral nerve regeneration 109 , it fails to do so in several models of CNS injury 110,111 . Conversely, JUN overexpression can promote regeneration in cultured cortical 110,112,113 and DRG neurons 114 ; however, as described above, its activation downstream of DLK also promotes cell death in RGCs 66 . Whereas neuronal JUN is clearly necessary for peripheral axon regeneration 115 , JNK-mediated phosphorylation of JUN appears to not be required for its full function in facial nerve regeneration 116 .…”
Section: Transcriptional Changesmentioning
confidence: 90%
See 3 more Smart Citations
“…Although overexpression of ATF3 can promote peripheral nerve regeneration 109 , it fails to do so in several models of CNS injury 110,111 . Conversely, JUN overexpression can promote regeneration in cultured cortical 110,112,113 and DRG neurons 114 ; however, as described above, its activation downstream of DLK also promotes cell death in RGCs 66 . Whereas neuronal JUN is clearly necessary for peripheral axon regeneration 115 , JNK-mediated phosphorylation of JUN appears to not be required for its full function in facial nerve regeneration 116 .…”
Section: Transcriptional Changesmentioning
confidence: 90%
“…Bioinformatics approaches to integrate discoveries related to regenerative capacity across multiple laboratories could help to drive drug discovery, but such studies remain difficult to interpret because of the lack of cell-type-specific data. Although a recent study identified pathways and small molecules that can enhance growth of injured neurons 114 , the effects observed were small, and future multilevel bioinformatics analyses will benefit from novel neuron-specific data sets. Furthermore, how injured neurons can reprogramme themselves to regrow their axons while maintaining their competency to form synapses and how they can stop growth once regeneration is complete is still not understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful axonal regeneration employs networks of interrelated genes concomitant to the activated state of the neuron, including transcription activators and functional networks related to growth-specific signaling pathways [3][4][5][6][7] . A recent study using RNA sequencing technology indicated that successfully regenerating peripheral neurons coordinately express genes within regeneration networks 8 . This coordinated regulation of molecules is considered a hallmark feature of successful regeneration.…”
Section: Intrinsic Mechanismsmentioning
confidence: 99%